2020
DOI: 10.2196/18896
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Breast Cancer e-Support Program for Chinese Women With Breast Cancer Undergoing Chemotherapy (Part 3): Secondary Data Analysis

Abstract: Background Many app-based interventions targeting women with breast cancer have been developed and tested for effectiveness. However, information regarding the evaluation of the usage of these interventions is scarce. A better understanding of usage data is important to determine how women use apps and how these interventions affect health outcomes. Objective This study aimed to examine the usage duration and login frequency of an app-based intervention… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 38 publications
3
47
0
Order By: Relevance
“… 60 , 64 Most primarily focused on QOL 37 , 43 - 47 , 49 , 50 , 55 , 57 - 61 , 68 or mental health (depressive symptoms, anxiety symptoms, and distress), 38 , 43 , 48 , 56 , 62 , 65 , 66 and some on physical health (physical activity, fatigue, and nutrition) 34 , 57 , 61 or self-efficacy. 39 , 64 , 71 Process evaluations were collected in 25/32 (78.1%) studies (Data Supplement 1). 34 - 36 , 38 , 39 , 41 - 50 , 52 , 53 , 56 - 59 , 61 , 62 , 64 - 67 , 69 , 71 , 72 Measurement details (questionnaires and domains) and data inclusions and exclusions for the meta-analyses are presented in Data Supplements 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 60 , 64 Most primarily focused on QOL 37 , 43 - 47 , 49 , 50 , 55 , 57 - 61 , 68 or mental health (depressive symptoms, anxiety symptoms, and distress), 38 , 43 , 48 , 56 , 62 , 65 , 66 and some on physical health (physical activity, fatigue, and nutrition) 34 , 57 , 61 or self-efficacy. 39 , 64 , 71 Process evaluations were collected in 25/32 (78.1%) studies (Data Supplement 1). 34 - 36 , 38 , 39 , 41 - 50 , 52 , 53 , 56 - 59 , 61 , 62 , 64 - 67 , 69 , 71 , 72 Measurement details (questionnaires and domains) and data inclusions and exclusions for the meta-analyses are presented in Data Supplements 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…60,64 Most primarily focused on QOL 37,[43][44][45][46][47]49,50,55,[57][58][59][60][61]68 or mental health (depressive symptoms, anxiety symptoms, and distress), 38,43,48,56,62,65,66 and some on physical health (physical activity, fatigue, and nutrition) 34,57,61 or self-efficacy. 39,64,71 Process evaluations were collected in 25/32 (78.1%) studies (Data Supplement 1). [34][35][36]38,39,[41][42][43][44][45][46][47][48][49][50]52,53,[56][57][58]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There was one mixed-method study [19] and two study protocols [16,20]. Five randomized controlled trials (RCTs) [13][14][15]17,18], one nonrandomized controlled prospective cohort study [12], as well as one secondary data analysis of RCT [21] were identified. The earliest study dated from 2016 [13], and the most recent was published in 2021 [15].…”
Section: Resultsmentioning
confidence: 99%
“…Positive correlation of Cancer e-Support Program usage duration with self-efficacy (r = 0.290, p = .03), social support (r = 0.320, p = .02), and quality of life (r = 0.273, p = .04) at 3 months. 2020, China [21] Secondary data analysis of the multicentre, singleblinded, RCT [18] Intervention group from RCT [18] Mobile nutritional aspects of care via the app was efficiently integrated in clinical routine [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation